Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Sikap Keuangan Terhadap Kinerja Usaha dan Keberlangsungan UMKM di Indonesia - Dwi Rachmadini, Nabilla; Rimbano, Dheo; Safitri, Tiansi; Chobil Ardian, Ahmad; Apriyani, Krisma; Ferdiansyah, Joni; Chah Yuni, Cici (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
A review was conducted in Indonesia with the purpose of determining the impact of financial literacy, financial inclusion, and financial attitudes on the performance and sustainability of UMKM businesses. The results of this review are presented in this article. According to the findings of earlier studies in the same field. The review covers the years 2016–2024 and is based on results from Systematic Literature Reviews (SLRs) conducted using Google Scholar. The study found that financial literacy, financial inclusion, and financial attitudes all had an impact on UMKM's business performance and sustainability.